Tyrosine kinase signalling in breast cancer: Epidermal growth factor receptor - convergence point for signal integration and diversification - Prenzel, Norbert (BioMed Central, 2000)
Cross-communication between different signalling systems is critical for the integration of multiple and changing environmental influences on individual cells. The epidermal growth factor receptor (EGFR) has been identified as a key element in the complex signalling network that is utilized by various classes of cell-surface receptors. This nonclassical mode of signalling system cross-talk, in distinction to receptor activation induced by cognate ligands, has been termed 'signal transactivation'. With the EGFR as the convergence point and distribution focus, this scenario may involve signals emitted by other members of the tyrosine kinase family, cytokine receptors, ion channels, G-protein-coupled receptors and integrins.